The Fallacies of Lord Keynes' General Theory: Comment - Tobin, James (Quarterly Journal of Economics, 1948)
Journal Article The Fallacies of Lord Keynes' General Theory: Comment Get access James Tobin James Tobin Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 5, November 1948, Pages 763–770, https://doi.org/10.2307/1883470 Published: 01 November 1948